Market Versus Society Anthropological Insights (Palgrave Studies in Urban Anthropology, 2018)
This volume addresses the fraught relationship between market and society in times of social and economic crisis, exploring how they interact in key social, cultural, and political arenas on a global scale. The contributors examine the neoliberal market in anthropological and ethnographic terms to question whether "market logic" has won out against social aspects of human existence in a framework of minimal state protection and the devaluation of human labor. Fruitfully combining empirical data and theoretical approaches, the volume investigates the extent to which ordinary people accept unequal allocations of resources and examines their sense of belonging in an expansive neoliberal economy.